Experimental demonstration of an optimised PWM scheme for more even device electro-thermal stress in a 3-Level ANPC GaN inverter - Zeng, Y.; Gurpinar, Emre; Hussein, A.; Castellazzi, Alberto (2018)
GaN device as one potential power electronics device has been gained much attention recently. One of the power conversion systems, ANPC inverter using GaN HEMT is potentially considered to be prospective usage of low loss and high efficiency. In this work, we demonstrate one optimised PWM scheme aims at balancing the device electro-thermal stress based on Parma PWM to control 3-Level ANPC GaN inverter. The method is to decrease the loss for switches account for the large loss and increase the loss for switches with less thermal stress initially. The simulation and experimental results prove the effectiveness of the optimised PWM in controlling the loss distribution.